THE INTERLEUKIN-6-174 G/C AND 572 G/C PROMOTER POLYMORPHISM ASSOCIATED WITH HIGH RISK OF ORAL PRE CANCER AND CANCER IN NORTH INDIAN POPULATION. Issue 8 (2016) - Gupta, Shalini; KumudNigam, KumudNigam; M.L.B.Bhatt, M.L.B.Bhatt; Mahdi, Abbas Ali
No abstract available